Influences of solid-state brazing conditions on microstructure and tensile shear force of Ag-Cu-P brazed copper sheets - P Jattakul; K Kanlayasiri (My University, 2018)
This study aimed to examine the tensile shear force and microstructure of copper sheets when Ag-Cu-P filler metal was applied for the joints involved in the production of laminated micro-channel array (LMA) devices. The properties of the microstructure of the Ag- Cu-P/copper brazed joints were examined following a process which included furnace brazing, with the parameters comprising temperature, holding time, and loading pressure. Analytical tools included an energy dispersive spectrometer (EDS), scanning electron microscope (SEM) and X-ray diffraction analysis (XRD). In addition, tensile tests were performed to measure the tensile shear force. It was difficult to observe the Cu3P which forms along with the layer between the Ag-Cu-P filler metal and the copper sheet when the brazing temperature was only 580?C since this allowed gaps to form within the joint, thus producing very low tensile shear force results. When the brazing temperature is increased to 620?C along with longer holding time and increased pressure, this allows a thicker phase of Cu3P to form in the brazing joint. With a holding time of 30 minutes and pressure of 12.173 kPa, tensile shear force was maximized since this condition produced thick Cu3P phase. It is apparent that it is possible to produce a brazed joint which has an average shear force of 736.27 N under these conditions as described above. Within the joint could be found a Cu3P phase with no brittle phase.
Keywords: Brazing; Shear Strength; Electronic Packaging and Soldering Technologies